2020
DOI: 10.3390/nu12041139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Omega-3 and Vitamin D Supplement on Fatty Acids and Vitamin D Serum Levels in Double-Blinded, Randomized, Controlled Trials in Healthy and Crohn’s Disease Populations

Abstract: Two trials separately measured the bioavailability and impact on inflammation of a supplement taken daily containing 510 mg Docosahexaenoic acid (DHA), 344 mg Eicosapentaenoic acid (EPA), and 1000 IU of vitamin D (25-hydroxyvitamin D; 25(OH)D), for healthy and Crohn’s disease (CD) populations. Both trials were double blinded, randomized, placebo-controlled with cross-over. Participants were randomly allocated to groups A (placebo then supplement) or B (supplement then placebo). Both included a washout. Fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…[5] found that fish oil preparation that limits the side effects of traditional fish oil therapy shows promise as an adjunctive treatment for Crohn's disease. Omega 3 fatty acids reduce intestinal inflammation, induce and maintain clinical remission in UC patients, and are related with the reduction of pro inflammatory cytokines, decrease disease activity and increase the quality of life of CD patients [4,32]. In conclusion, since results of our study showed that omega 3 given orally had beneficial effects on Crohn's rats, so, it could be recommended that omega 3 supplementation might be worthy protecting for Crohn's disease patients.…”
Section: Resultsmentioning
confidence: 61%
“…[5] found that fish oil preparation that limits the side effects of traditional fish oil therapy shows promise as an adjunctive treatment for Crohn's disease. Omega 3 fatty acids reduce intestinal inflammation, induce and maintain clinical remission in UC patients, and are related with the reduction of pro inflammatory cytokines, decrease disease activity and increase the quality of life of CD patients [4,32]. In conclusion, since results of our study showed that omega 3 given orally had beneficial effects on Crohn's rats, so, it could be recommended that omega 3 supplementation might be worthy protecting for Crohn's disease patients.…”
Section: Resultsmentioning
confidence: 61%
“…Additionally, supplementation with krill oil, probiotics, and vitamin D decreased inflammation in mice [32]. Dual supplementation of n-3 FAs and vitamin D in more severe cases of inflammatory disease may lack effects, as this showed no effect on hs-CRP in healthy and Crohn's disease populations [33]. Here, we hypothesize that a dietary supplement consisting of probiotics, EPA + DHA, and vitamin D would help combat systemic inflammation in individuals with overweight and obesity by strengthening the intestinal barrier.…”
Section: The Potential Of Dietary Supplementsmentioning
confidence: 99%
“…However, ω-3 fatty acids exhibit contradictory effects. Combined supplementation of ω-3 fatty acids and vitamin D does not significantly improve CD inflammation and clinical remission ( 226 ). Multicenter randomized controlled trials have demonstrated the ineffectiveness of using free ω-3 fatty acids for preventing CD relapse ( 227 ).…”
Section: Therapeutic Approaches Based On Fatty Acidsmentioning
confidence: 99%